Implicit alcohol–relaxation associations in frequently drinking adolescents with high levels of neuroticism. (June 2015) - Salemink, E.; van Lier, P.A.C.; Meeus, W.; Raaijmakers, S.F.; Wiers, R.W.
Abstract: Introduction: Most individuals start drinking during adolescence, a period in which automatically activated or implicit cognitive processes play an important role in drinking behavior. The aim of this study was to examine personality-related antecedents of implicit associations between alcohol and positive or negative reinforcement motives in adolescents. It was hypothesized that frequent alcohol consumption in combination with specific personality traits (neuroticism for negative reinforcement and extraversion for positive reinforcement) could predict specific implicit alcohol–relaxation and arousal associations. Methods: Participants completed a brief Big Five Questionnaire and alcohol use questions at T1. Approximately eight months later (T2), two Brief Implicit Association Tests were completed to assess alcohol–relaxation (negative reinforcement, n  = 222) and alcohol–arousal (positive reinforcement, n  = 248) associations. Results: Results indicated that frequently drinking adolescents who scored high on neuroticism had the strongest alcohol–relaxation associations eight months later. No significant predictors were observed for alcohol–arousal associations. Conclusions: The current study identified precursors of strong implicit alcohol–relaxation associations (i.e., high levels of neuroticism in combination with frequent alcohol consumption) which can inform future prevention and intervention studies. Highlights: Implicit processes play, especially in adolescence, an important role in drinking. Knowledge of antecedents of implicit alcohol associations is limited. The current study examined personality-related antecedents in adolescents. Strongest alcohol-relaxation associations for neuroticism with frequent drinking. Precursors of implicit processes allow identification of risk groups.